2017
DOI: 10.3201/eid2308.162039
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization ofCorynebacterium diphtheriaeOutbreak Isolates, South Africa, March–June 2015

Abstract: In 2015, a cluster of respiratory diphtheria cases was reported from KwaZulu-Natal Province in South Africa. By using whole-genome analysis, we characterized 21 Corynebacterium diphtheriae isolates collected from 20 patients and contacts during the outbreak (1 patient was infected with 2 variants of C. diphtheriae). In addition, we included 1 cutaneous isolate, 2 endocarditis isolates, and 2 archived clinical isolates (ca. 1980) for comparison. Two novel lineages were identified, namely, toxigenic sequence typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 30 publications
0
34
0
Order By: Relevance
“…This strain was toxigenic and unrelated to the nontoxigenic strain that was isolated in the outbreak. Furthermore, when this ST was compared to other historical, non-outbreak-associated South African isolates and other documented C. diphtheria isolates worldwide, the outbreak strain was not related [38].…”
Section: Molecular Diagnostics and Typing In South African Surveillanmentioning
confidence: 86%
“…This strain was toxigenic and unrelated to the nontoxigenic strain that was isolated in the outbreak. Furthermore, when this ST was compared to other historical, non-outbreak-associated South African isolates and other documented C. diphtheria isolates worldwide, the outbreak strain was not related [38].…”
Section: Molecular Diagnostics and Typing In South African Surveillanmentioning
confidence: 86%
“…Subspecies diphtheriae and lausannense correspond to lineage-1 and 2, respectively (Bolt et al, 2010 ; Grosse-Kock et al, 2017 ). Since the term “lineage” was also used for other ST types that are part of lineage-1 (du Plessis et al, 2017 ), we think that the use of subspecies could reduce confusion in the literature and help the reader to recognize clades showing these large genomic differences. An ANI cutoff of 95-96% has been proposed to distinguish between two bacterial species (Kim et al, 2014 ) and ANI values between subspecies lausannense and subspecies diphtheriae fall exactly within this range (Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Isolates belonging to lineage-2 were previously documented on 4 continents, showing a worldwide distribution of subspecies lausannense (Bolt et al, 2010 ; Farfour et al, 2013 ) (Data Sheet 3). Interestingly, several studies reported only lineage-1 (subspecies diphtheriae ) isolates, suggesting that lineage-2 is less frequently encountered (Zasada, 2013 ; du Plessis et al, 2017 ; Grosse-Kock et al, 2017 ), as does the observation that ST affiliated to subspecies lausannense represent <15% of known ST.…”
Section: Discussionmentioning
confidence: 99%
“…The diphtheria cases in particular countries varied and determined by some local factors including coverage of vaccination, education level, and socioeconomic condition (Galazka 2000). WHO reported that during 2016 there were 7.097 diphtheria cases globally in which India, Indonesia, and Madagascar countries had the highest number of diphtheria cases (Clarke 2018). In Indonesia, outbreaks of diphtheria have increased from 2010 to 2017 (MoH-RI 2017).…”
Section: Introductionmentioning
confidence: 99%